KEPASTIAN HUKUM BAGI KORBAN TINDAK PIDANA MANIPULASI DATA OTENTIK DALAM KASUS KEJAHATAN CYBER PUTUSAN PENGADILAN NEGERI JAKARTA SELATAN(Studi Putusan 786/Pid.B/2022/PN Jkt.Sel) - Bambang Hartono; Suta Ramadhan, Nathaniel Benecia Simanjuntak (JOURNAL OF LAW AND NATION, 2024)
Forgery comes from the word fake which means "inauthentic, illegitimate, imitation, fake, while forgery is still from the same source defined as the process, method, act of counterfeiting". Factors causing perpetrators to commit criminal acts of manipulating authentic data in Cyber crime cases decided by the South Jakarta District Court (Study Decision Number: 786/Pid.B/2022/PN Jkt.Sel). and Criminal Responsibility of Perpetrators of Criminal Acts of Manipulating Authentic Data in Cyber Crime Cases South Jakarta District Court Decision (Study Decision Number: 786/Pid.B/2022/PN Jkt.Sel). The research method used in this thesis research is a normative juridical approach and an empirical approach. Based on the research results obtained, it can be concluded that the factors causing the perpetrator to commit the crime of manipulating authentic data in the cyber crime case, the decision of the South Jakarta District Court (Study Decision Number: 786/Pid.B/2022/PN Jkt.Sel). influenced by bad economic factors alone are the main factors causing criminal acts of forgery of letters, but the presence of human greed and weak individual faith and morals are also the driving force for criminal acts of forgery of letters committed by the perpetrators. and Criminal Responsibility of Perpetrators of the Crime of Manipulating Authentic Data In the Cyber Crime Case Decision of the South Jakarta District Court (Study Decision Number: 786/Pid.B/2022/PN Jkt.Sel). which was imposed by the defendant with a prison sentence of 1 (one) year, lighter than the demands of the Public Prosecutor who demanded that the defendant be imprisoned for 2 years